Factors Associated with Quality of Life of Type II DM Patients - Ahmad Apriyanto; Muhammad Romadhon; Erik Rosadi (Poltekkes Kemenkes Tasikmalaya, 2025)
Type II diabetes mellitus (DM) is a chronic disease whose prevalence continues to increase worldwide. According to the World Health Organization (WHO, 2023) in Mariang (2023), type II DM is a leading cause of global morbidity and mortality, with a health burden that increases annually.International Diabetes Federation(IDF Diabetes, 2021) reported that the number of people with diabetes in Indonesia in 2021 reached 19.5 million and is expected to increase to 28.6 million by 2045. This condition has various impacts on health, one of which is a decrease in the patient's quality of life. The Indonesian Ministry of Health (2022) emphasized that the management of DM patients does not only focus on controlling blood glucose levels, but also on improving the quality of life. This study aims to analyze factors related to the quality of life of type II DM patients at the Burnay Mulya Community Health Center, including duration of suffering, level of knowledge, family support, and dietary adherence. The study used a quantitative design with a cross-sectional approach. The sample consisted of 67 respondents selected using random sampling. The research instruments were questionnaires on quality of life, knowledge, family support, and dietary adherence. Data analysis was performed using the Chi-Square test at a significance level of 0.05. The results showed a significant relationship between quality of life and duration of illness (p=0.031), knowledge (p=0.036), family support (p=0.008), and dietary adherence (p=0.024). Therefore, it can be concluded that the quality of life of type II diabetes patients is influenced by these factors. Healthcare professionals are expected to increase education, patient empowerment, and family support efforts to improve the quality of life of diabetes patients